Pengembangan Kreativitas Sebagai Pembentukan Karakter Anak Usia Dini - Diana Indah Palupi; Emma Rahmani; Erlin Yusnita; Hera Gustina; Hikmah Pertiwi; Nurbani Chalid (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2023)
Mayesty (1990) states that creativity is a way of thinking and acting or creating something original and valuable/useful for that person and others. Creativity according to Santrock (2002) is the ability to think about things in new and unusual ways and give birth to a unique solution to the problems encountered. In line with what was stated by Gallagher (in Munandar, 1999) revealed that creativity is related to the ability to create, organize, find a new form and or to produce something through imaginative skills, this means that creativity is related to the experience of expressing and actualizing individual identity in the form of integrated in relationship with oneself, with nature and with others. Creativity is a product of ideas or solutions that are new and useful. According to Munandar (2002) one of the benefits of creativity is that it can improve the quality of life and solve problems from various points of view, therefore creativity is important to be honed from an early age, so that it becomes an inherent character in children. In relation to the formation of the character of early childhood, we can see together that the character of the Indonesian nation has deviated a lot from norms, both legal norms, social norms, and even religious norms. People today are experiencing a crisis that has such a great impact on civilization, namely the crisis of character. Seeing this fact, the initial foundation for the realization of a character that fits the profile of Pancasila must be developed from an early age. Through the development of creativity, it is hoped that the formation of character in children can be done from an early age. Character education was chosen as an effort to realize the character formation of students or the nation's generation of noble character. This study uses a qualitative research type with reference to descriptive analysis from various relevant sources as well as a study of research results that raise the theme of the relationship between creativity development in developing the character of early childhood. The type of study used is literature study by collecting information from books, journals, discussion of articles and others. From the results of this study, it is known that the development of creativity in early childhood has a very good impact on the character development process.